An investigation of the factors influencing consumers' buying behaviour of the low-cost carriers in Malaysia - Beg, Mirza Kashif (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2018)
This study investigates the factors influencing consumers' buying behaviour of Low-Cost Carriers (LCCs) in Malaysia. Nowadays, LCCs are particularly popular all over the world due to the cost compensation rather than smooth services. In Malaysia, LCCs are economic carrier because of short distance, flight ticket price, straight forward sales, almost moderate model airplane, and wide range of network hubs. However, large number of LCCs in Malaysia has increased competition and conflict among the airline consumers. As such, this research was carried out to overcome the conflicts by reducing the knowledge gap in the marketing field, especially on the factors influencing the consumers' buying behaviour of LCCs. Therefore, the researcher has adopted quantitative research design and used survey questionnaire to collect data from 206 students who are consumer of low-cost carrier in Malaysia. While developing the questionnaire used for data collection for this study, the six independent variables considered are price, service quality, reputation, safety, route availability, and promotion; the dependent variable on the other hand is consumers' buying behaviour. Having analysed the data collected from the respondents using multiple regression analysis, it was found that price, route availability, and promotion are positively and significantly contributed to the consumers' buying behaviour of low-cost carrier in Malaysia. Based on these findings, the researcher has rejected three hypotheses out of six hypotheses developed for this study. Therefore, the researcher is of the opinion that the suggestions offered in this study would encourage the LCCs companies to improve in the area of price, route availability, and promotion so as to encourage more travelers to select them; this is expected to contribute to growth of LCCs in Malaysia.